In margine al «Lazarillo de Tormes»: la formazione dell’antieroe (Carte Romanze, 2024)
The contribution aims to highlight some aspects of Lazarillo de Tormes: the weight of the previous literary elements, Spanish and foreign; the parodic reference to some principles by Francesco Guicciardini; the circular structure of the story.
Keywords: Lazarillo de Tormes; picaresque narrative; literary criticism